Fábulas Esópicas, introducción, traducción y notas por F. Martín García y A. Róspide López, Madrid, Alba, 1989, 299 pp. ISBN 84-7567-600-6 (Minerva, 2019)
Review: Fábulas Esópicas, introducción, traducción y notas por F. Martín García y A. Róspide López, Madrid, Alba, 1989, 299 pp. ISBN 84-7567-600-6